Effectuation in digital multi-sided platform startups: An entrepreneurial journey through open innovation process - Adhi Setyo Santoso (Digital Business, 2024)
A paradox arises in platform-based open innovation, wherein digital Multi-Sided Platform (MSP) firms with little initial co-creation ability can successfully adopt an open innovation strategy that typically requires a high level of co-creation capacity. This study aims to fill this gap by theoretically exploring the connection between effectuation, which involves entrepreneurial action based on a given set of means and the selection of possible effects, and the open innovation process with co-creation capacity. The objective is to contribute to the significant growth of digital MSP startups. This study investigates the process of open innovation based on platforms in the context of resource constraints, limited knowledge, and uncertainty. The outcomes of a quantitative study including 70 digital MSP startups indicate that the most efficient route for these businesses to achieve Innovation Performance is by first developing Effectuation, followed by Integrative Capabilities and Co-Creation Capacity, and last, Innovation Performance. However, in this shortest path, the involvement of Crowds or Communities Management Practices plays a role in partially moderating the relationship between Effectuation and Integrative Capabilities. Platform-based innovation serves as the point of integration between effectuation theory in entrepreneurship research and open innovation strategy in strategic management research. The bridge connecting these two fields has significant implications for research on platform-based innovation in the field of strategic entrepreneurship.
Keywords: 650; Co-creation capacity; Crowds or communities-based open innovation; Effectuation; Integrative capabilities; Multi-sided platform; Platform-based open innovation